STRATEGI PUBLIC RELATIONS “CHIKI TWIST” DALAM MENINGKATKAN BRAND AWARENESS - Aldila Dense; A Sigit Pramono Hadi (UNIVERSITAS PAKUAN, 2022)
Chiki, which had suspended for 8 years in the 2010 era, has been in Indonesia since 1980. In 2021, Chiki released a snack innovation called Chiki Twist. The extruded snack which is made of corn flour requires a public relations (PR) strategy to increase brand awareness. Through the communicating #PlayTheCircleofFun, Chiki Twist communicates that it is a playmate among the daily activities by its target market. The purpose of this research is to find out how the PR strategy of Chiki Twist as a new brand increases brand awareness. The research method is descriptive qualitative research with data collection techniques, in-depth interviews and focus group discussions (FGD). The results of the study reveals that Chiki Twist carried out both offline and online PR strategies. The PR strategies implemented were sampling, bundling, and education. While the PR strategy was online (digital), Chiki Twist focused on digital assets on Instagram, TikTok, YouTube, and Twitter. In this digital asset, Chiki Twist communicated value and positioning in the form of content. Other support run on digital was also using media ads, micro influencers, macro influencers, to increase awareness. Consumers have received the message communicated by Chiki Twist. The results state that the PR strategy to increase awareness which was conducted by Chiki Twist has been successful.